2002
DOI: 10.4049/jimmunol.169.10.5904
|View full text |Cite
|
Sign up to set email alerts
|

A Protease-Activated Pathway Underlying Th Cell Type 2 Activation and Allergic Lung Disease

Abstract: The respiratory allergens that induce experimental Th cell type 2-dependent allergic lung inflammation may be grouped into two functional classes. One class of allergens, in this study termed type I, requires priming with adjuvants remote from the lung to overcome airway tolerogenic mechanisms that ordinarily preclude allergic responses to inhaled Ags. In contrast, the other, or type II, allergen class requires neither remote priming nor additional adjuvants to overcome airway tolerance and elicit robust aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
295
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(315 citation statements)
references
References 78 publications
14
295
0
6
Order By: Relevance
“…Live A. fumigatus was also shown to downregulate the proinflammatory function of mouse airway DCs exposed to mite allergens (67). In contrast, other studies rather suggested that ASP treatment leads to partially matured DCs, driving a Th2 cell polarization with IL-4 and IL-5 production (68) and allergic lung inflammation in mice (69). Reasons for these discrepancies are presently unclear but could be due to fungal strain differences or to the impact of ASP on other cells beyond DCs, such as basophils or epithelial cells, which in those experimental systems could contribute to Th2 polarization (70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
“…Live A. fumigatus was also shown to downregulate the proinflammatory function of mouse airway DCs exposed to mite allergens (67). In contrast, other studies rather suggested that ASP treatment leads to partially matured DCs, driving a Th2 cell polarization with IL-4 and IL-5 production (68) and allergic lung inflammation in mice (69). Reasons for these discrepancies are presently unclear but could be due to fungal strain differences or to the impact of ASP on other cells beyond DCs, such as basophils or epithelial cells, which in those experimental systems could contribute to Th2 polarization (70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
“…Allergic airway allergic inflammation was induced in mice as described (Kheradmand et al, 2002). Briefly, mice were anesthetized with isoflurane vapor (IsoFlo, Abbot-USA) and allowed to inhale 50 μL of a PBS suspension containing 5 μg of Aspergillus oryzae proteinase (Sigma) and 25 μg of ovalbumin (Sigma).…”
Section: Murine Airway Inflammationmentioning
confidence: 99%
“…Many allergens relevant to human diseases, such as fungi, mite, cockroach, and pollens, have protease activities (29); these protease activities of allergens potently induce Th2-type immune responses in several experimental animal models (19,20). Our results provide a mechanistic understanding for these protease-related observations when AECs are exposed to environmental allergens.…”
Section: Discussionmentioning
confidence: 73%
“…Certain allergens are also proteases (e.g., Amb a from ragweed pollen; Bla g from cockroach; Asp f 5, f 6, and f 11 from Aspergillus; and Der p 1, p 3, p 9 from house dust mite [HDM]) (1). The protease activities produced by HDM, Aspergillus, or ragweed promoted a Th2 response (19,20). HDM proteases can activate protease-activated receptors (PARs), leading to allergic inflammation (21-23).…”
mentioning
confidence: 99%